Lexical metaphors in Minyak Pengalun: Unveiling the ecological and cultural identity of Karo tradition - Tarigan, Karisma Erikson; Sibarani, Robert; Widayati, Dwi; Dardanila, Dardanila (Research Journal in Advanced Humanities, 2025)
The purpose of this study is to determine how the Karo people’s ecological and cultural identity is reflected and constructed through lexical metaphors, as found in Minyak Pengalun. This study used a qualitative study design, gathering data through semi-structured interviews with community elders and traditional healers, and document analysis of cultural texts about Karo customs. The metaphors were identified, categorised, and interpreted using methods of metaphor analysis. Nature as a Healer, Purity and Traditional Wisdom, Cultural Continuity and Heritage, Integration and Unity, Ritual and Traditional Knowledge, and Spirituality and Talent are the six categories of metaphors of equality that the results show. These analogies define Minyak Pengalun as a profound cultural artefact that represents the Karo community’s fusion of nature, culture, and spirituality, going beyond its status as a form of medicine. The Minyak Pengalun metaphors indicate the continuation of cultural practices that emphasise ecological harmony by reflecting the Karo people’s reverence for the environment and knowledge as conveyed via a worldview. This study advances knowledge about the importance of language and traditional expressions in preserving the ecological and cultural legacy of indigenous groups, such as the Karo people.